COVID-19, TERHADAP EKSISTENSI PELAKU USAHA - Nanda Hidayan Sono (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2020)
This research has the aim to find and analyze the impact of the Covid-19 pandemic on the existence of businesses in East Java. The research method in this study uses descriptive qualitative methods. Data sources are more focused on secondary data sources derived from the results of research as well as sources of reference literature in accordance with the discussion with the research conducted. The time interval for conducting research was conducted from April to June 2020. Data collection techniques used were documentation techniques. The results showed that the impact of the Covid-19 pandemic was grouped into 2 parts. First, Covid-19 Pandemic is one of the biggest factors that has an impact on business actors, especially those who depend their lives through direct meetings with consumers / buyers. Second, business categories constrained by the Covid-19 pandemic include MSMEs, hospitality and tourism, restaurants, shopping centers, transportation and property sectors. Third, business categories that increased during the Covid-19 pandemic include the health sector (masks, hand sanitizers, disinfectants, face shields, medicines, vitamins, etc.), food delivery and logistics, Information Technology, food processing and, retail. Fourth, business actors in the business category are constrained due to the Covid-19 pandemic can move to businesses that fall into the increased business category by utilizing available online business platforms or marketplaces.